Alternative activation generates IL-10 producing type 2 innate lymphoid cells - Corey R. Seehus (Nature Portfolio, 2017)
Type 2 innate lymphoid cells (ILC2) are thought to be a uniform population of effector cells that produce IL-5 and IL-13. Here, the authors shown that, in mice, IL-33 can alternatively activate these cells to generate a molecularly distinct IL-10-producing subset designated ILC210.